Biological Properties of Tinospora crispa (Akar Patawali) and Its Antiproliferative Activities on Selected Human Cancer Cell Lines - Amom, Zulkhairi; Md Akim, Abdah; Nik Hassan, Mohd Kamal; Ibrahim, Nursakinah; Mohd Moklas, Mohamad Aris; Bahari, Hasnah; Fazil, Muhammad Nor Fazali; Fairuz Azman, Khairunnuur; Abdul Kadir, Khairul Kamilah; Md Shah, Zamree; Mohd Arshad, Mohd Shahidan (Nutrition Society of Malaysia, 2008)

(untitled)
The antioxidant and anti-proliferative activity of the aqueous crude extract of Tinospora crispa stem was investigated. The proximate composition of its stem and leaves was determined. Proximate analysis revealed that T. crispa contains - protein: leaves = 4.7%, stem = 1.2%; fat: leaves = 1.5%, stem = 0.43%; carbohydrate: leaves = 11.8%, stem = 19.4%; ash: leaves = 2.7%, stem = 1.1%; moisture: leaves = 79.3%, stem = 77.9%; fibre: leaves = 1.59%, stem = 0.65%; and energy: leaves = 1.59%, stem = 0.65%. The antioxidant activity of the extract prepared at various temperatures and incubation time was evaluated to determine the optimum extraction procedure. Based on DPPH and TBA tests, the preparation of the extract at 60oC for 6 hours was established as the best possible method as it demonstrated the highest inhibition percentage. The extract was tested against brine shrimp to evaluate its toxicity and no significant toxicity was recorded since the IC50 value was more than 1000 μg/ml. The extract produced moderate anti-proliferative activity on selected human cancer cell lines (IC50 MCF-7: 107 μg/ml, HeLa: 165 μg/ml, Caov-3: 100 μg/ml, and HepG2: 165 μg/ml). The findings from this study suggest that T. crispa has the potential to be a source of natural antioxidants and nutrients, besides having a moderate anti-proliferative effect on selected human cancer cell lines.